2020
DOI: 10.21203/rs.3.rs-25530/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Long noncoding RNA RP11-757G1.5 sponges miR-139-5p and upregulates YAP1 thereby promoting the proliferation and liver, spleen metastasis of colorectal cancer

Abstract: Background: Accumulating evidence indicates that long non-coding RNAs (lncRNAs) acting as crucial regulators in tumorigenesis. However, its biological functions of lncRNAs in colorectal cancer (CRC) have not been systematically clarified.Methods: An unbiased screening was performed to identify disregulated lncRNAs revealed to be implicated in CRC carcinogenesis according to an online-available data dataset. In situ hybridization (ISH), RT-qPCR and RNA fluorescence in situ hybridization (RNA-FISH) were applied … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…CeRNAs mediate gene expression and are assumed to function through MREs to form a transcriptional regulatory network in which mRNAs, pseudogenes and lncRNAs may 'interact' with each other, which may affect the progression of certain diseases (33,34). Studies have shown that ceRNAs serve pivotal roles in the invasion, proliferation and metastasis of cancer cells (35,36) and have confirmed that lncRNAs are also involved in regulating tumor ceRNA networks (37)(38)(39)(40). The present study found that lncKRT16P6 was located mainly in the cytoplasm of TSCC cells and acted as a sponge for miR-3180.…”
Section: Discussionmentioning
confidence: 99%
“…CeRNAs mediate gene expression and are assumed to function through MREs to form a transcriptional regulatory network in which mRNAs, pseudogenes and lncRNAs may 'interact' with each other, which may affect the progression of certain diseases (33,34). Studies have shown that ceRNAs serve pivotal roles in the invasion, proliferation and metastasis of cancer cells (35,36) and have confirmed that lncRNAs are also involved in regulating tumor ceRNA networks (37)(38)(39)(40). The present study found that lncKRT16P6 was located mainly in the cytoplasm of TSCC cells and acted as a sponge for miR-3180.…”
Section: Discussionmentioning
confidence: 99%